The distribution of coagulation factors VII and VIII and fibrinogen in adults over 65 years. Results from the Cardiovascular Health Study. - Tracy, R P; Bovill, E G; Fried, L P; Heiss, G; Lee, M H; Polak, J F; Psaty, B M; Savage, P J (Ann Epidemiol, 1992)
The Cardiovascular Health Study (CHS) was designed to examine cardiovascular disease and its risk factors in older adults. We report here the distributions of the coagulation factors fibrinogen, factor VII, and factor VIII in a population-based cohort of men and women 65 years or older. In other studies of middle-aged individuals, these factors were shown to be associated with cardiovascular risk. In the CHS cohort, all three factors were elevated, compared to levels reported in middle-aged individuals, and fibrinogen and factor VIII values were higher in each successive age group; factor VII values, in contrast, declined slightly with age in the CHS cohort. Compared to white subjects, blacks had higher values for fibrinogen and factor VIII and lower values for factor VII. While women had markedly higher values for factor VII and factor VIII than men at all ages in the CHS, mean fibrinogen values were not different between men and women.
Keywords: African Continental Ancestry Group; Age Factors; Aged; Cardiovascular Diseases; Cohort Studies; Factor VII; Factor VIII; Female; Fibrinogen; Humans; Male; Middle Aged; Risk Factors

Eligibility for cholesterol referral in community-dwelling older adults. The Cardiovascular Health Study. - Manolio, T A; Furberg, C D; Wahl, P W; Tracy, R P; Borhani, N O; Gardin, J M; Fried, L P; O'Leary, D H; Kuller, L H (Ann Intern Med, 1992)
OBJECTIVES: To assess the proportion of community-dwelling adults aged 65 years or older who are eligible for referral for lipoprotein analysis and intervention according to the National Cholesterol Education Program (NCEP) guidelines. DESIGN: Cross-sectional study based on examinations and questionnaires collected in 1989 and 1990. SETTING: Four communities in the U.S. in the Cardiovascular Health Study (CHS), a study of risk factors for heart disease and stroke in older adults. PARTICIPANTS: A sample of 4810 men and women ages 65 to 100 randomly selected and recruited from Health Care Financing Administration Medicare eligibility lists for the four communities; not institutionalized, not wheelchair-bound, not currently receiving therapy for cancer, not currently taking lipid-lowering medications, and not having eaten in the preceding 9 hours. MEASUREMENTS: Total cholesterol and lipoprotein analysis measured in all participants. RESULTS: Total cholesterol levels were less than 5.17 mmol/L (200 mg/dL) in 37% of participants, 5.17 to 6.19 mmol/L (200 to 239 mg/dL) in 39%, and 6.20 mmol/L (240 mg/dL) or greater in 24%. Compared with their counterparts, older participants, especially those over 80 years of age, were more likely to have levels below 5.17 mmol/L, as were men, nonwhites, and those with coronary heart disease or two or more coronary heart disease risk factors (P less than 0.008 for all values). Based on this screening measurement, 2174 participants were eligible for lipoprotein analysis, 80% were eligible for dietary or drug therapy using NCEP guidelines. Overall, 46% of CHS participants were eligible for lipoprotein analysis and 36% for intervention by NCEP guidelines, based on a single cholesterol measurement. CONCLUSION: A substantial proportion of older adults in this community sample were eligible for lipoprotein analysis and intervention. Prospective studies of elderly persons are needed to determine the risk for incident coronary heart disease according to NCEP classifications and the benefits of lipid-lowering treatments in persons in this age group so that intervention strategies may best be targeted to an appropriately high-risk group.
Keywords: Age Factors; Aged; Aged, 80 and over; Cerebrovascular Disorders; Cholesterol, LDL; Coronary Disease; Eligibility Determination; Female; Humans; Hypercholesterolemia; Longitudinal Studies; Male; Primary Prevention; Referral and Consultation; Risk Factors; United States

Lipoprotein lipids in older people. Results from the Cardiovascular Health Study. The CHS Collaborative Research Group. - Ettinger, W H; Wahl, P W; Kuller, L H; Bush, T L; Tracy, R P; Manolio, T A; Borhani, N O; Wong, N D; O'Leary, D H (Circulation, 1992)
BACKGROUND: Cardiovascular disease is the leading cause of death and disability in older people. There is little information about the distributions of risk factors in older populations. This article describes the distribution and correlates of lipoprotein lipids in people greater than or equal to 65 years old. METHODS AND RESULTS: Lipoprotein lipid concentrations were measured in 2,106 men (M) and 2,732 women (F) who were participants in the Cardiovascular Health Study, a population-based epidemiological study. Distributions of lipids by age and sex and bivariate and multivariate relations among lipids and other variables were determined in cross-sectional analyses. Mean concentrations of lipids were cholesterol: M, 5.20 +/- 0.93 mmol/l (201 +/- 36 mg/dl) and F, 5.81 +/- 0.98 mmol/l (225 +/- 38 mg/dl); triglyceride (TG): M, 1.58 +/- 0.85 mmol/l (140 +/- 75 mg/dl) and F, 1.57 +/- 0.78 mmol/l (139 +/- 69 mg/dl); high density lipoprotein cholesterol (HDL-C): M, 1.23 +/- 0.33 mmol/l (48 +/- 16 mg/dl), and F, 1.53 +/- 0.41 mmol/l (59 +/- 16 mg/dl); low density lipoprotein cholesterol (LDL-C): M, 3.27 +/- 0.85 mmol/l (127 +/- 33 mg/dl) and F, 3.57 +/- 0.93 mmol/l (138 +/- 36 mg/dl). The total cholesterol to HDL-C ratios were M, 4.49 +/- 1.29 and F, 4.05 +/- 1.22. TG, total cholesterol, and LDL-C concentrations were lower with increasing age, the last more evident in men than in women. TG concentration was positively associated with obesity (in women), central fat patterning, glucose intolerance, use of beta-blockers (in men), and use of estrogens (in women) and negatively associated with age, renal function, alcohol use, and socioeconomic status. In general, HDL-C had opposite relations with these variables, except that estrogen use was associated with higher HDL-C concentrations. LDL-C concentration was associated with far fewer variables than the other lipids but was negatively associated with age in men and women and positively correlated with obesity and central fat patterning and negatively correlated with renal function and estrogen use in women. There were no differences in total cholesterol and LDL-C concentrations among participants with and without prevalent coronary heart disease and stroke, but TG concentration was higher and HDL-C lower in men with both coronary heart disease and stroke and in women with coronary heart disease. CONCLUSIONS: Cholesterol and cholesterol/HDL-C ratio were lower and HDL-C higher than previously reported values in older people, suggesting that lipid risk profiles may be improving in older Americans. TG and HDL-C concentrations, and to a lesser extent LDL-C, were associated with potentially important modifiable factors such as obesity, glucose intolerance, renal function, and medication use.
Keywords: Aged; Aging; Cardiovascular Diseases; Cardiovascular Physiological Phenomena; Cholesterol, HDL; Cholesterol, LDL; Cross-Sectional Studies; Female; Health Status; Humans; Lipids; Lipoproteins; Male; Multivariate Analysis; Triglycerides

Associations of postmenopausal estrogen use with cardiovascular disease and its risk factors in older women. The CHS Collaborative Research Group. - Manolio, T A; Furberg, C D; Shemanski, L; Psaty, B M; O'Leary, D H; Tracy, R P; Bush, T L (Circulation, 1993)
BACKGROUND: Postmenopausal estrogen replacement therapy has been associated with favorable levels of cardiovascular disease risk factors, but these associations and the relations between estrogen use and subclinical disease have not been examined in large samples of older women. METHODS AND RESULTS: Present and past estrogen use was ascertained in 2955 women > or = 65 years old in the Cardiovascular Health Study, a study of risk factors for coronary heart disease and stroke in the elderly. Present estrogen use was reported by 12% of these women and past use by an additional 26.5%. Estrogen use (past or present) was strongly associated with lower low-density lipoprotein cholesterol, fibrinogen, glucose, insulin, obesity, and age and higher high-density lipoprotein cholesterol and socioeconomic status (all P < .0001). Estrogen users also had lower levels of subclinical disease as measured by carotid intimal-medial thickness, carotid stenosis grade, ECG left ventricular mass, and Doppler mitral peak flow velocities (each P < .02). Relations were similar in younger and older women (65 to 74 versus > or = 75 years) and smokers and nonsmokers and were unchanged after women with poor medication compliance were excluded. After adjustment for other factors, estrogen use was associated with decreased carotid wall thickness, although this association was of borderline significance after further adjustment for lipids. CONCLUSIONS: Postmenopausal estrogen use in this sample of older women was associated with favorable cardiovascular disease risk factor profiles and with lower measures of subclinical disease. These findings suggest that postmenopausal estrogen use may be associated with lower risk of cardiovascular disease in women well into the eighth decade of life.
Keywords: Aged; Aging; Cardiovascular Diseases; Carotid Arteries; Carotid Stenosis; Electrocardiography; Estrogen Replacement Therapy; Female; Heart; Heart Ventricles; Humans; Patient Compliance; Risk Factors; Smoking; Ultrasonography

Epidemiology of low cholesterol levels in older adults. The Cardiovascular Health Study. - Manolio, T A; Ettinger, W H; Tracy, R P; Kuller, L H; Borhani, N O; Lynch, J C; Fried, L P (Circulation, 1993)
BACKGROUND: Low cholesterol levels have been associated with increased mortality from stroke, cancer, and other noncardiovascular diseases, but the reasons for this association remain unclear. One explanation is that persons with low cholesterol levels have early or occult disease that eventually leads to their deaths. METHODS AND RESULTS: This possibility was explored in 2,091 men and 2,714 women 65-100 years old in the Cardiovascular Health Study, a multicenter observational study of risk factors for heart disease and stroke in older adults. Cholesterol levels < or = 160 mg/dL were present in 11.6% of men and 3.7% of women and increased in prevalence with age. After adjustment for age, total cholesterol levels in this range were associated with a twofold increased prevalence of treated diabetes in men and women and with a twofold increased prevalence of cancer diagnosed in the preceding 5 years in women only. Low cholesterol was also associated with lower levels of hemoglobin, albumin, and factor VII, suggesting a link with hepatic synthetic function. On multivariate analysis, factors most strongly associated with low cholesterol levels in men and women were decreased factor VII levels, decreased albumin, and diabetes. CONCLUSIONS: Cross-sectional associations with low cholesterol levels differ by sex and suggest poorer health by some measures. The observed relations with treated diabetes and impaired hepatic synthetic function should be examined for risk of mortality in longitudinal data from this and other observational studies.
Keywords: Aged; Aged, 80 and over; Aging; Cardiovascular Diseases; Cardiovascular Physiological Phenomena; Cholesterol; Female; Health Status; Humans; Longitudinal Studies; Male; Prevalence; Probability; Regression Analysis; Risk Factors

Prevalence of cardiovascular diseases among older adults. The Cardiovascular Health Study. - Mittelmark, M B; Psaty, B M; Rautaharju, P M; Fried, L P; Borhani, N O; Tracy, R P; Gardin, J M; O'Leary, D H (Am J Epidemiol, 1993)
The Cardiovascular Health Study is a population-based longitudinal study of 5,201 adults aged 65 years and older. Prevalences of myocardial infarction, angina pectoris, congestive heart failure, peripheral artery disease, stroke, and transient ischemic attack were ascertained between June 1989 and May 1990 in participants recruited from Forsyth County, North Carolina; Washington County, Maryland; Sacramento County, California; and Pittsburgh, Pennsylvania. A medical history was taken to obtain self-reports of prevalent disease. For all participants, use of nitrates was ascertained to document angina, electrocardiograms were used to document prevalent myocardial infarction, and ankle-arm blood pressure studies were used to document peripheral artery disease. Self-reports of disease that were not confirmed by examination findings were further investigated by examination of medical records. Reported disease that was confirmed by examination findings or by medical records was classified as "definite." Disease that was documented by examination, but not reported by the participant, was classified as "unreported." The prevalence rates of definite myocardial infarction and angina were 11% and 15%, respectively, among men aged 65-69 years, 18% and 17% among men aged 80-84 years, 4% and 8% among women aged 65-69 years, and 3% and 13% among women aged 80-84 years. Twenty-three percent of men and 38% of women with electrocardiographic evidence of myocardial infarction did not report it. These results suggest that prevalent disease estimates based only on self-report may underestimate the prevalence of cardiovascular diseases in older Americans.
Keywords: Age Factors; Aged; Aged, 80 and over; Bias; California; Cardiovascular Diseases; Electrocardiography; Female; Health Surveys; Humans; Longitudinal Studies; Male; Maryland; Mass Screening; North Carolina; Pennsylvania; Population Surveillance; Prevalence; Reproducibility of Results

Sonographic evaluation of carotid artery atherosclerosis in the elderly: relationship of disease severity to stroke and transient ischemic attack. - Polak, J F; O'Leary, D H; Kronmal, R A; Wolfson, S K; Bond, M G; Tracy, R P; Gardin, J M; Kittner, S J; Price, T R; Savage, P J (Radiology, 1993)
Doppler and real-time ultrasound (US) were performed to evaluate the extent of atherosclerotic changes in the carotid artery and to assess their relationship to prevalent cerebrovascular disease. Real-time US scans and Doppler measurements of the carotid arteries were analyzed in 5,201 subjects aged 65 years or older. Severity of atherosclerotic lesions was associated with increased frequencies of hyperechoic, irregular, and heterogeneous textured lesions (P < .0001). The severity of internal carotid artery stenosis was associated with thickening of the intima-media layer of the common carotid artery wall (r = .37, P < .0001). A history of stroke and transient ischemic attack (TIA) was more likely when hyperechoic, heterogeneous, and irregular lesions were seen in the carotid artery. Internal carotid artery stenosis correlated better with prevalent stroke and TIA than did sonographic descriptions of plaque texture. However, the prevalence of hyperechoic, heterogeneous, and irregular lesions increased as the degree of internal carotid stenosis increased. On real-time images alone, the average of the internal carotid artery maximal wall thickness is the sonographic measure of atherosclerosis that enables the best prediction of prevalent stroke and TIA.
Keywords: Aged; Arteriosclerosis; Carotid Artery Diseases; Carotid Artery, Internal; Carotid Stenosis; Cerebrovascular Disorders; Female; Humans; Ischemic Attack, Transient; Male; Ultrasonography

Black-white differences in subclinical cardiovascular disease among older adults: the Cardiovascular Health Study. CHS Collaborative Research Group. - Manolio, T A; Burke, G L; Psaty, B M; Newman, A B; Haan, M; Powe, N; Tracy, R P; O'Leary, D H (J Clin Epidemiol, 1995)
Cardiovascular and all-cause mortality are higher in black than white Americans, but racial differences in clinical and subclinical cardiovascular disease (CVD) have not been examined in older adults. Clinical and subclinical CVD and its risk factors were compared in 4926 white and 244 black men and women aged 65 years and older. Black participants had lower socioeconomic status and generally higher prevalences of CVD and its risk factors, except for adverse lipid profiles. Common carotid wall thickness was greater in black than white women, and ankle-arm blood pressure ratios were lower in black women and men (p < 0.01). After adjustment for CVD risk factors, common carotid walls were significantly thicker and ankle-arm ratios were lower in blacks than whites of both sexes, while internal carotid walls were significantly thinner in black women. Racial differences in clinical and subclinical CVD in older adults are similar to those reported in younger populations and do not appear to be explained by CVD risk factors.
Keywords: African Continental Ancestry Group; Aged; Cardiovascular Diseases; Carotid Arteries; European Continental Ancestry Group; Female; Geriatric Assessment; Humans; Male; Multivariate Analysis; Prevalence; Regression Analysis; Risk Factors; Sex Factors

Association of fibrinogen and coagulation factors VII and VIII with cardiovascular risk factors in the elderly: the Cardiovascular Health Study. Cardiovascular Health Study Investigators. - Cushman, M; Yanez, D; Psaty, B M; Fried, L P; Heiss, G; Lee, M; Polak, J F; Savage, P J; Tracy, R P (Am J Epidemiol, 1996)
The cross-sectional correlates of three hemostatic factors--fibrinogen, factor VII, and factor VIII--were examined in the Cardiovascular Health Study, a population-based cohort study of 5,201 subjects over age 65 years. Subjects were recruited in 1989-1990 in Forsyth County, North Carolina; Sacramento County, California; Washington County, Maryland; and Pittsburgh, Pennsylvania. In multivariate linear regression models, cardiac risk factors significantly associated with fibrinogen were current smoking, race, lipids, and white blood count. In women, alcohol use, obesity, physical activity, and insulin level were also significant, while in men hypertension was correlated. The significant correlates of factor VII were lipids and white blood count in men and estrogen use, alcohol use, race, lipids, insulin level, white blood count, and obesity in women. The independent correlates of factor VIII were insulin, glucose, and race in both sexes; low density lipoprotein cholesterol, white blood count, and diuretic use in men; and alcohol use in women. In multivariate models, factors known to be modifiable risk factors for cardiovascular disease accounted for more of the population variance of these hemostatic factors in women than in men, especially for factor VII. The hemostatic factors may mediate some effects of risk factors on disease, and this should be considered in longitudinal studies.
Keywords: Age Distribution; Aged; Aged, 80 and over; Analysis of Variance; Cardiovascular Diseases; Cohort Studies; Factor VII; Factor VIII; Female; Fibrinogen; Humans; Linear Models; Logistic Models; Male; Prevalence; Risk Factors; Sex Distribution; United States

Asthma and its association with cardiovascular disease in the elderly. The Cardiovascular Health Study Research Group. - Enright, P L; Ward, B J; Tracy, R P; Lasser, E C (J Asthma, 1996)
Cardiovascular disease (CVD) is more prevalent in elderly than in middle-aged patients. Symptoms such as intermittent wheezing with dyspnea may then be due to either CVD or asthma. The objective of this study was to determine the prevalence and correlates of asthma in the elderly and their associations with CVD and CVD risk factors. A community sample of 5201 elderly persons from the Cardiovascular Health Study was asked if they had a physician diagnosis of asthma, and multiple cardiovascular risk and disease variables were measured. Six percent of the participants (309) recalled a history of asthma, and half of these were never smokers. Thirty percent of those with asthma were currently taking a bronchodilator, 14% inhaled steroids, and 10% oral prednisone. Men and women with asthma who were cigarette smokers were more likely to report a concurrent diagnosis of congestive heart failure than smokers without asthma (p = .04). However, when we determined the independent CVD correlates of asthma in this cohort, controlling for smoking status, age, gender, and diagnoses of chronic bronchitis and emphysema, only higher levels of high-density lipoprotein cholesterol (HDL-C) and higher plasma fibrinogen levels were significantly associated with asthma. It was concluded that asthma is as prevalent in the elderly as in middle-aged persons and is associated with higher HDL-C and higher fibrinogen levels, but not with prevalent cardiovascular disease.
Keywords: Aged; Aged, 80 and over; Asthma; Cardiovascular Diseases; Cohort Studies; Female; Humans; Lung; Male; Multivariate Analysis; Prevalence; Risk Factors; Sex Distribution; Smoking

Correlates of thrombin markers in an elderly cohort free of clinical cardiovascular disease. - Cushman, M; Psaty, B M; Macy, E; Bovill, E G; Cornell, E S; Kuller, L H; Tracy, R P (Arterioscler Thromb Vasc Biol, 1996)
Studies suggest that thrombosis is important in the progression of atherosclerotic lesions. The biochemical markers prothrombin fragment 1-2 and fibrinopeptide A reflect in vivo thrombin generation and activity, respectively. As such, they are markers that might be associated with cardiovascular risk. From the Cardiovascular Health Study, a cohort study of 5201 persons over 65 years of age, 399 persons free of clinical cardiovascular disease (CVD) at the baseline examination were selected for study of specialized markers of hemostasis. We report the cross-sectional relationships of the thrombin markers to CVD risk factors and measures of subclinical CVD. The range of fragment 1-2 2 was 0.12 to 0.85 nmol/L. The range of fibrinopeptide A was 0.9 to 44.1 micrograms/L. High levels of fragment 1-2 and fibrinopeptide A were associated with age, with levels higher in women than men. Fragment 1-2 was associated with smoking; high levels of triglyceride, creatinine, and C-reactive protein; and low levels of glucose. Fibrinopeptide A was associated with high C-reactive protein and apolipoprotein(a) and lower ankle-brachial index. There were no significant associations of the thrombin markers with race, fibrinogen, alcohol consumption, diabetes, or most measures of subclinical CVD. Study findings support a hypothesis that there are physiological interrelationships between cardiac risk factors, hemostasis, inflammation, and progression of atherosclerosis.
Keywords: Aged; Biomarkers; Cardiovascular Diseases; Cohort Studies; Female; Hemostasis; Humans; Male; Risk Factors; Thrombin

Current estrogen-progestin and estrogen replacement therapy in elderly women: association with carotid atherosclerosis. CHS Collaborative Research Group. Cardiovascular Health Study. - Jonas, H A; Kronmal, R A; Psaty, B M; Manolio, T A; Meilahn, E N; Tell, G S; Tracy, R P; Robbins, J A; Anton-Culver, H (Ann Epidemiol, 1996)
The cardioprotective effects of combined estrogen/progestin replacement therapy have been questioned. Therefore, we have compared carotid arterial wall thickening and the prevalence of carotid stenosis in elderly women (> or = 65 years old) currently using replacement estrogen/progestins (E + P) with arterial pathology and its prevalence in women using unopposed estrogens (E). This cross-sectional study used baseline data from all 2962 women participating in the Cardiovascular Health Study, a population-based study of coronary heart disease and stroke in elderly adults. Users of hormone replacement therapy (HRT) were categorized as never (n = 1726), past (n = 787), current E (n = 280), or current E + P (n = 73). Maximal intimal-medial thicknesses of the internal and common carotid arteries and stenosis of the internal carotid arteries were measured by ultrasonography. Current E + P users resembled current E users in most respects, although some lifestyle factors were more favorable among E + P users. Current E + P use and current E use (as compared with no use) were associated with smaller internal carotid wall thicknesses (-0.22 mm; P = 0.003; and -0.09 mm; P = 0.05, respectively) and smaller common carotid wall thicknesses (-0.05 mm; P = 0.03; and -0.02 mm; P = 0.1, respectively) and lower odds ratios (OR) for carotid stenosis (> or = 1% vs. 0%); OR = 0.61; 95% confidence interval [CI]: 0.36 to 1.01; and OR = 0.91, 95% CI: 0.67 to 1.24, respectively), after adjustment for current lifestyle and risk factors. When both groups of current HRT users were compared, there were no significant differences in carotid wall thicknesses or prevalence of carotid stenosis. For this sample of elderly women, both current E + P therapy and current E therapy were associated with decreased measures of carotid atherosclerosis. These measures did not differ significantly between the two groups of HRT users.
Keywords: Aged; Arteriosclerosis; Carotid Arteries; Carotid Stenosis; Cohort Studies; Confidence Intervals; Cross-Sectional Studies; Databases, Factual; Drug Therapy, Combination; Estrogen Replacement Therapy; Estrogens; Female; Health Status Indicators; Humans; Odds Ratio; Progestins; Reproductive History; Ultrasonography; United States; Women's Health

Lipoprotein levels in elderly patients with asthma. Cardiovascular Health Study Research Group. - Enright, P L; Lasser, E C; Ward, B J; Tracy, R P (J Allergy Clin Immunol, 1996)
Keywords: Aged; Aging; Arteriosclerosis; Asthma; Female; Humans; Lipoproteins; Male; Prospective Studies; Risk Factors; Sex Factors

Diabetes mellitus and echocardiographic left ventricular function in free-living elderly men and women: The Cardiovascular Health Study. - Lee, M; Gardin, J M; Lynch, J C; Smith, V E; Tracy, R P; Savage, P J; Szklo, M; Ward, B J (Am Heart J, 1997)
This report describes the relation among diabetes, blood pressure, and prevalent cardiovascular disease, and echocardiographically measured left ventricular mass and filling (transmitral valve flow) velocities in the Cardiovascular Health Study, a cohort of 5201 men and women > or = 65 years of age. Ventricular septal and left posterior wall thicknesses were greater in diabetic than in nondiabetic subjects, showing a significant linear trend (p = 0.025 for ventricular septal thickness in both sexes combined, p = 0.002 for posterior wall thickness) with increased duration of diabetes. Increased wall thickness of the ventricular septum or the left posterior wall was not associated with prevalent coronary heart disease (CHD) in the cohort. Increased left ventricular mass was associated with diabetic persons not reporting CHD and with all subjects with CHD regardless of glucose tolerance status. After adjusting for body weight, blood pressure, heart rate, and prevalent coronary or cerebrovascular disease, diabetes (as measured by glucose level, insulin use, oral hypoglycemic use, and a positive history of diabetes before baseline examination) remained an independent predictor of increased left ventricular mass among men and women (174.2 gm in diabetic men vs 169.8 gm in normal men, 138.2 gm in diabetic women vs 134.0 gm in normal women, p = 0.043 for both sexes combined). Both early and late diastolic transmitral peak flow velocities were higher with increased duration of diabetes, but the calculated ratio of the early peak flow velocity to the late velocity (E/A ratio) did not differ significantly between subjects with historical diabetes and those with normal fasting glucose (both genders combined, p = 0.190). Glucose level, insulin use, oral hypoglycemic use, and a positive history of diabetes before baseline examination were significant independent predictors of the late transmitral peak flow velocity and its integrated flow-velocity curve but not for the integral of the early peak flow velocity or the E/A ratio. Diabetes is associated with abnormal left ventricular structure and function in elderly persons. This association persists after adjustment for body weight, blood pressure, heart rate, and reported coronary or cerebrovascular disease.
Keywords: Aged; Blood Flow Velocity; Blood Pressure; Diabetes Mellitus; Echocardiography; Female; Glucose Tolerance Test; Humans; Male; Mitral Valve; Residence Characteristics; Ventricular Function, Left

Lifetime smoking exposure affects the association of C-reactive protein with cardiovascular disease risk factors and subclinical disease in healthy elderly subjects. - Tracy, R P; Psaty, B M; Macy, E; Bovill, E G; Cushman, M; Cornell, E S; Kuller, L H (Arterioscler Thromb Vasc Biol, 1997)
Blood levels of C-reactive protein (CRP), a marker of inflammation, are related to cardiovascular disease risk. To determine cross-sectional correlates in the elderly, we measured CRP in 400 men and women older than 65 years and free of clinical cardiovascular disease at baseline as part of the Cardiovascular Health Study. Only 2% of the values were greater than 10 mg/L, the cut-point usually used to identify inflammation. CRP levels appeared tightly regulated, since there were strong bivariate correlations between CRP and the following: inflammation-sensitive proteins such as fibrinogen (r = .52); measures of fibrinolysis such as plasmin-antiplasmin complex (r = .23); pack-years of smoking (r = .30); and body mass index (r = .24; all P values < or = .001). The association with pack-years was independent of the length of time since cessation of smoking. CRP levels were also associated with coagulation factors VIIc, IXc, and Xc; HDL cholesterol (negative) and triglyceride; diabetes status; diuretic use; ECG abnormalities; and level of exercise. Because of effect modification, two multiple linear regression prediction models were developed for CRP, one each for never smokers and ever smokers. An a priori physiologic model was used to guide these analyses, which disallowed the use of other inflammation-sensitive variables such as fibrinogen. In never smokers, the independent predictors were body mass index (+), diabetes status (+), plasmin-antiplasmin complex (+), and the presence of ECG abnormalities (+); this model predicted 15% of the CRP population variance. In ever smokers, the predictors were body mass index (+), plasmin-antiplasmin complex (+), pack-years of smoking (+), HDL cholesterol (-), and ankle-arm blood pressure index (-); this model predicted 42% of the population variance. We conclude that levels of CRP in the healthy elderly are tightly regulated and reflect lifetime exposure to smoking as well as level of obesity, ongoing level of fibrinolysis, diabetes status, and level of subclinical atherothrombotic disease. Moreover, exposure to smoking affects the relation of CRP to these other factors.
Keywords: Aged; Body Mass Index; C-Reactive Protein; Cardiovascular Diseases; Female; Humans; Male; Multivariate Analysis; Risk Factors; Smoking

Relationship of C-reactive protein to risk of cardiovascular disease in the elderly. Results from the Cardiovascular Health Study and the Rural Health Promotion Project. - Tracy, R P; Lemaitre, R N; Psaty, B M; Ives, D G; Evans, R W; Cushman, M; Meilahn, E N; Kuller, L H (Arterioscler Thromb Vasc Biol, 1997)
Markers of inflammation, such as C-reactive protein (CRP), are related to risk of cardiovascular disease (CVD) events in those with angina, but little is known about individuals without prevalent clinical CVD. We performed a prospective, nested case-control study in the Cardiovascular Health Study (CHS; 5201 healthy elderly men and women). Case subjects (n = 146 men and women with incident CVD events including angina, myocardial infarction, and death) and control subjects (n = 146) were matched on the basis of sex and the presence or absence of significant subclinical CVD at baseline (average follow-up, 2.4 years). In women but not men, the mean CRP level was higher for case subjects than for control subjects (P < or = .05). In general, CRP was higher in those with subclinical disease. Most of the association of CRP with female case subjects versus control subjects was in the subgroup with subclinical disease; 3.33 versus 1.90 mg/L, P < .05, adjusted for age and time of follow-up. Case-control differences were greatest when the time between baseline and the CVD event was shortest. The strongest associations were with myocardial infarction, and there was an overall odds ratio for incident myocardial infarction for men and women with subclinical disease (upper quartile versus lower three quartiles) of 2.67 (confidence interval [CI] = 1.04 to 6.81), with the relationship being stronger in women (4.50 [CI = 0.97 to 20.8]) than in men (1.75 [CI = 0.51 to 5.98]). We performed a similar study in the Rural Health Promotion Project, in which mean values of CRP were higher for female case subjects than for female control subjects, but no differences were apparent for men. Comparing the upper quintile with the lower four, the odds ratio for CVD case subjects was 2.7 (CI = 1.10 to 6.60). In conclusion, CRP was associated with incident events in the elderly, especially in those with subclinical disease at baseline.
Keywords: Aged; Aging; C-Reactive Protein; Cardiovascular Diseases; Case-Control Studies; Female; Humans; Male; Prospective Studies; Sex Factors

Correlates of antithrombin, protein C, protein S, and TFPI in a healthy elderly cohort. - Sakkinen, P A; Cushman, M; Psaty, B M; Kuller, L H; Bajaj, S P; Sabharwal, A K; Boineau, R; Macy, E; Tracy, R P (Thromb Haemost, 1998)
The majority of fatal acute myocardial infarctions occur in the elderly. Since these events are predominantly thrombotic, we studied the cross-sectional associations of the anticoagulant proteins Antithrombin, Protein C, Protein S. and Tissue Factor Pathway Inhibitor (TFPI) in a subgroup (n = 400) of the Cardiovascular Health Study (a study of healthy men and women > or = 65 years) free of clinical cardiovascular disease (CVD). We did not observe any strong age-associated trends, although Protein C was lower in older women (p < or = 0.001), and TFPI was higher in older men (p < or = 0.01). The inhibitors were highly intercorrelated, and were associated with increased levels of inflammation-sensitive proteins (e.g., fibrinogen. plasminogen), lipids (especially total and LDL-cholesterol), and coagulation factors, such as Factors VIIc, IXc, and Xc. None was associated with the procoagulant markers Prothrombin Fragment F1-2 or Fibrinopeptide A. Only TFPI was associated with subclinical atherosclerosis: ankle-arm index and internal carotid artery stenosis, p trend < or = 0.01; and carotid wall thickness, p trend < or = 0.05. In multivariate analysis the independent predictors of TFPI were levels of fibrinogen; the fibrinolytic marker plasmin-antiplasmin complex; LDL-cholesterol; and carotid wall thickness (R2 for the model = 0.35). In summary, the inhibitors did not appear to increase with age, and were predominantly associated with inflammation markers and lipids. Since markers of thrombin production do increase with age, we hypothesize that an age-related hemostatic imbalance may ensue, with associated increased thrombotic risk. Only TFPI was associated with subclinical CVD, suggesting that it may more closely reflect endothelial damage.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Anticoagulants; Antithrombin III; Biomarkers; Cross-Sectional Studies; Disease Susceptibility; Female; Humans; Lipoproteins; Male; Prevalence; Protein C; Protein S; Reference Values; Risk Factors; Thrombosis

Diabetes in older adults: comparison of 1997 American Diabetes Association classification of diabetes mellitus with 1985 WHO classification. - Wahl, P W; Savage, P J; Psaty, B M; Orchard, T J; Robbins, J A; Tracy, R P (Lancet, 1998)
BACKGROUND: We aimed to compare the prevalence of abnormal glucose tolerance identified by the 1985 WHO and the 1997 American Diabetes Association (ADA) diagnostic categories based on information collected in the Cardiovascular Health Study, an epidemiological study of elderly people. METHODS: We measured glucose concentrations during fasting and 2 h after a 75 g oral glucose-tolerance test in participants aged 65-100 years in the Cardiovascular Health Study. From a 1989 cohort, we analysed the glucose measurements of 4515 individuals without a previous diagnosis of diabetes and of 262 additional measurements from an African-American cohort recruited in 1992-93. FINDINGS: In the 1989 cohort, the prevalence of untreated diabetes with ADA diagnostic fasting criteria was 7.7% versus a prevalence of 14.8% by the WHO criteria. In the African-American cohort, the prevalence of untreated diabetes was 2.7% with ADA criteria and 11.8% with WHO criteria. 3509 (77.7%) of the 4515 participants in the 1989 cohort had normal glucose concentrations according to ADA fasting criteria, compared with 2401 (53.2%) according to WHO criteria. In the African-American cohort, the corresponding numbers were 239 (91.2%) versus 153 (58.4%). All differences in prevalence of abnormal glucose tolerance between ADA and WHO classifications were significant (p<0.0001). INTERPRETATION: Among elderly individuals, there was a significant difference in the prevalence of diabetes identified by the WHO diagnostic criteria based on oral glucose-tolerance test and the ADA fasting criteria. Consequently, many individuals currently classified as non-diabetic according to ADA criteria would previously have had a diagnosis of diabetes according to WHO criteria. Longitudinal studies are needed to assess the value of the criteria in the identification of individuals at increased risk of diabetes-associated chronic complications.
Keywords: African Americans; Aged; Aged, 80 and over; Cohort Studies; Diabetes Mellitus; Female; Glucose Tolerance Test; Humans; Male; Prevalence; Societies, Medical; World Health Organization

Factor V Leiden is not a risk factor for arterial vascular disease in the elderly: results from the Cardiovascular Health Study. - Cushman, M; Rosendaal, F R; Psaty, B M; Cook, E F; Valliere, J; Kuller, L H; Tracy, R P (Thromb Haemost, 1998)
Coagulation factor V Leiden is a risk marker for venous thrombosis. For arterial thrombosis no large study to date has included population-based elderly patients. The Cardiovascular Health Study is a longitudinal study of 5,201 men and women over age 65. With 3.4-year follow-up, we studied 373 incident cases of myocardial infarction (MI), angina, stroke. or transient ischemic attack (TIA), and 482 controls. The odds ratios for each event with heterozygous factor V Leiden were: MI, 0.46 (95% CI 0.17 to 1.25); angina, 1.0 (95% CI 0.45 to 2.23); stroke, 0.77 (95% CI 0.35 to 1.70): TIA, 1.33 (95% CI 0.5 to 3.55); any outcome, 0.83 (95% CI 0.48 to 1.44). Adjustment for cardiovascular risk factors did not change relationships. In older adults factor V Leiden is not a risk factor for future arterial thrombosis.
Keywords: Adult; Age Factors; Aged; Arteries; Factor V; Female; Humans; Male; Middle Aged; Mutation; Risk Factors; Thrombosis

Analytical and biologic variability in measures of hemostasis, fibrinolysis, and inflammation: assessment and implications for epidemiology. - Sakkinen, P A; Macy, E M; Callas, P W; Cornell, E S; Hayes, T E; Kuller, L H; Tracy, R P (Am J Epidemiol, 1999)
An increasing number of cardiovascular epidemiologic studies are measuring non-traditional risk markers of disease, most of which do not have established biovariability characteristics. When biovariability data have been reported, they usually represent a short time period, and, in any case, there is little consensus on how the information should be used. The authors performed a long-term (6-month) repeated measures study on 26 healthy individuals, and, using a nested analysis of variance (ANOVA) approach, report on the analytical (CVA), intraindividual (CVI), and between individual (CVG) variability of 12 procoagulant, fibrinolysis, and inflammation assays, including total cholesterol for comparison. The results suggest acceptable analytical variability (CVA < or = 1/2 CVI) for all assays. However, there was a large range of intraindividual variation as a proportion of total variance (2-78%), and adjusting for intraindividual and between individual variation in bivariate correlations increased the observed correlation by more than 30 percent for three of these assays. Overall, the assays showed a significant increase in intraindividual variation over 6 months (p < 0.05). While these findings suggest that most of these assays have biovariability characteristics similar to cholesterol, there is variation among assays. Some assays may be better suited to epidemiologic studies, and knowledge of an assay's biovariability data may be useful in interpreting simple statistics, and in designing multivariate models.
Keywords: Adult; Aged; Analysis of Variance; Cardiovascular Diseases; Cholesterol; Epidemiology; Female; Fibrinolysis; Hemostasis; Humans; Inflammation; Male; Middle Aged; Models, Statistical; Multivariate Analysis; Risk Factors

Fibrinolytic activation markers predict myocardial infarction in the elderly. The Cardiovascular Health Study. - Cushman, M; Lemaitre, R N; Kuller, L H; Psaty, B M; Macy, E M; Sharrett, A R; Tracy, R P (Arterioscler Thromb Vasc Biol, 1999)
Coagulation factor levels predict arterial thrombosis in epidemiological studies, but studies of older persons are needed. We studied 3 plasma antigenic markers of fibrinolysis, viz, plasminogen activator inhibitor-1 (PAI-1), fibrin fragment D-dimer, and plasmin-antiplasmin complex (PAP) for the prediction of arterial thrombosis in healthy elderly persons over age 65. The study was a nested case-control study in the Cardiovascular Health Study cohort of 5201 men and women >/=65 years of age who were enrolled from 1989 to 1990. Cases were 146 participants without baseline clinical vascular disease who developed myocardial infarction, angina, or coronary death during a follow-up of 2.4 years. Controls remained free of cardiovascular events and were matched 1:1 to cases with respect to sex, duration of follow-up, and baseline subclinical vascular disease status. With increasing quartile of D-dimer and PAP levels but not of PAI-1, there was an independent increased risk of myocardial infarction or coronary death, but not of angina. The relative risk for D-dimer above versus below the median value (>/=120 microg/L) was 2.5 (95% confidence interval, 1.1 to 5.9) and for PAP above the median (>/=5.25 nmol/L), 3.1 (1.3 to 7.7). Risks were independent of C-reactive protein and fibrinogen concentrations. There were no differences in risk by sex or presence of baseline subclinical disease. D-dimer and PAP, but not PAI-1, predicted future myocardial infarction in men and women over age 65. Relationships were independent of other risk factors, including inflammation markers. Results indicate a major role for these markers in identifying a high risk of arterial disease in this age group.
Keywords: Age Factors; Aged; Angina Pectoris; Biomarkers; Female; Fibrin Fibrinogen Degradation Products; Fibrinolysin; Fibrinolysis; Follow-Up Studies; Heart Arrest; Humans; Male; Myocardial Infarction; Plasminogen Activator Inhibitor 1; Risk Factors

Hormone replacement therapy, inflammation, and hemostasis in elderly women. - Cushman, M; Meilahn, E N; Psaty, B M; Kuller, L H; Dobs, A S; Tracy, R P (Arterioscler Thromb Vasc Biol, 1999)
Lipid-lowering by postmenopausal hormone therapy (HRT) explains only partly the assumed coronary risk reduction associated with therapy. To explore other possible mechanisms, we studied associations of HRT use with inflammation and hemostasis risk markers in women >/=65 years of age. Subjects were selected from 3393 participants in the fourth year examination of the Cardiovascular Health Study, an observational study of vascular disease risk factors. After excluding women with vascular disease, we compared levels of inflammation and hemostasis variables in the 230 women using unopposed estrogen and 60 using estrogen/progestin, with those of 196 nonusers selected as controls. Compared with nonusers, unopposed estrogen use was associated with 59% higher mean C-reactive protein (P<0.001), but with modestly lower levels of other inflammation indicators, fibrinogen, and alpha-1 acid glycoprotein (P<0.001). Factor VIIc was 16% higher among estrogen users (P<0.001), but this was not associated with higher thrombin production (prothrombin fragment 1-2), or increased fibrin breakdown (D-dimer). Concentration of plasminogen activator inhibitor-1 was 50% lower in both using groups (P<0.001) compared with nonusers, and this was associated with higher plasmin-antiplasmin complex: 8% higher in estrogen and 18% higher in estrogen/progestin users (P<0. 05). Relationships between the markers and hormone use were less pronounced in estrogen/progestin users, with no association for C-reactive protein except in women in upper 2 tertiles of body mass index (P for interaction, 0.02). The direction and strength of the associations of HRT use with inflammation markers differed depending on the protein, so it is not clear whether HRT confers coronary risk reduction through an inflammation-sensitive mechanism. Associations with hemostasis markers indicated no association with evidence of procoagulation and a possible association with increased fibrinolytic activity.
Keywords: Aged; Biomarkers; Case-Control Studies; Cross-Sectional Studies; Estrogens; Female; Hemostasis; Hormone Replacement Therapy; Humans; Inflammation; Progestins; Random Allocation; United Kingdom; United States

Increased blood glucose and insulin, body size, and incident colorectal cancer. - Schoen, R E; Tangen, C M; Kuller, L H; Burke, G L; Cushman, M; Tracy, R P; Dobs, A; Savage, P J (J Natl Cancer Inst, 1999)
BACKGROUND: Abdominal obesity--an elevated level of visceral adipose tissue--has been linked to colorectal cancer. Furthermore, elevated levels of visceral adipose tissue have been associated with hyperinsulinemia, and insulin is a growth factor in the colon. We assessed whether waist circumference, a surrogate measure of visceral adipose tissue, and metabolic parameters associated with visceral adipose tissue were related to colorectal cancer. METHODS: In the Cardiovascular Health Study cohort, we examined the relationship of baseline measurements of body size, glucose, insulin, and lipoproteins to incident colorectal cancer. All P values are two-sided. RESULTS: Among 5849 participants, 102 incident cases of colorectal cancer were identified. Individuals in the highest quartile of fasting glucose had a nearly twofold increased risk of colorectal cancer (relative risk [RR] = 1.8; 95% confidence interval [CI] = 1.0-3.1), and the linear trend RR (LT RR = 1.2; 95% CI = 1.0-1.5) for fasting glucose level was statistically significant (P =. 02). Glucose and insulin levels 2 hours after oral glucose challenge also exhibited statistically significant associations with colorectal cancer (2-hour glucose levels: RR = 2.4 [95% CI = 1.2-4. 7]/LT RR = 1.3 [95% CI = 1.0-1.6; P =.02]; 2-hour insulin levels: RR = 2.0 [95% CI = 1.0-3.8]/LT RR = 1.2 [95% CI = 1.0-1.5; P =.04]). Analysis of fasting insulin levels suggested a threshold effect, with values above the median associated with colorectal cancer (RR = 1.6; 95% CI = 1.1-2.4; P =.02). Higher levels of waist circumference were also statistically significantly associated with colorectal cancer (RR = 1.9; 95% CI = 1.1-3.3; P =.02). CONCLUSIONS: These data provide, to our knowledge, the first direct evidence of an association between elevated visceral adipose tissue level, its associated metabolic effects, and colorectal cancer.
Keywords: Adipose Tissue; Aged; Blood Glucose; Body Constitution; Cholesterol, HDL; Colorectal Neoplasms; Female; Humans; Incidence; Insulin; Male; Prospective Studies; Risk; Triglycerides; Viscera

The relationship of fibrinogen and factors VII and VIII to incident cardiovascular disease and death in the elderly: results from the cardiovascular health study. - Tracy, R P; Arnold, A M; Ettinger, W; Fried, L; Meilahn, E; Savage, P (Arterioscler Thromb Vasc Biol, 1999)
Little is known about the prospective associations of fibrinogen, factor VII, or factor VIII with cardiovascular disease (CVD) and mortality in the elderly. At baseline in the Cardiovascular Health Study (5888 white and African American men and women; aged >/=65 years), we measured fibrinogen, factor VIII, and factor VII. We used sex-stratified stepwise Cox survival analysis to determine relative risks (RRs) for CVD events and all-cause mortality (up to 5 years of follow-up), both unadjusted and adjusted for CVD risk factors and subclinical CVD. After adjustment, comparing the fifth quintile to the first, fibrinogen was significantly associated in men with coronary heart disease events (RR=2.1) and stroke or transient ischemic attack (RR=1.3), and also with mortality within 2.5 years of follow-up (RR=5.8) and later (RR=1.7). Factor VIII was significantly associated in men with coronary heart disease events (RR=1.5) and mortality (RR=1.8), and in women with stroke/transient ischemic attack (RR=1.4). For both factors, values were higher in those who died, whether causes were CVD-related or non-CVD-related, but highest in CVD death. Factor VII exhibited associations with incident angina (RR=1.44) in men and with death in women (RR, middle quintile compared with first=0.66). However, in general, factor VII was not consistently associated with CVD events in this population. We conclude that, if confirmed in other studies, the measurement of fibrinogen and/or factor VIII may help identify older individuals at higher risk for CVD events and mortality.
Keywords: Aged; Cardiovascular Diseases; Factor VII; Factor VIII; Female; Fibrinogen; Humans; Male; Multivariate Analysis; Risk Factors

Relationship of plasmin generation to cardiovascular disease risk factors in elderly men and women. - Sakkinen, P A; Cushman, M; Psaty, B M; Rodriguez, B; Boineau, R; Kuller, L H; Tracy, R P (Arterioscler Thromb Vasc Biol, 1999)
Plasmin-alpha2-antiplasmin complex (PAP) marks plasmin generation and fibrinolytic balance. We recently observed that elevated levels of PAP predict acute myocardial infarction in the elderly, yet little is known about the correlates of PAP. We measured PAP in 800 elderly subjects who were free of clinical cardiovascular disease in 2 cohort studies: the Cardiovascular Health Study and the Honolulu Heart Program. Median PAP levels did not differ between the Cardiovascular Health Study (6.05+/-1.46 nmol/L) and the Honolulu Heart Program (6.11+/-1.44 nmol/L), and correlates of PAP were similar in both cohorts. In CHS, PAP levels increased with age (r=0. 30), procoagulant factors (eg, factor VIIc, r=0.15), thrombin activity (prothrombin fragment F1+2, r=0.29), and inflammation-sensitive proteins (eg, fibrinogen, r=0.44; factor VIIIc, r=0.37). PAP was associated with increased atherosclerosis as measured by the ankle-arm index (AAI) (P for trend, </=0.001). PAP was negatively related to factors associated with the insulin resistance syndrome (IRS) (eg, fasting insulin, r=-0.26; body mass index, r=-0.26), possibly reflecting an association with plasminogen activator inhibitor-1 (r=-0.29). Although our study did not have sufficient power to detect a significant interaction, PAP and AAI appeared to be more weakly associated in subjects with more manifestations of the IRS: PAP appeared more strongly associated with AAI in the subgroup with 0 or 1 metabolic disorders (P</=0.001; slope estimate, -0.14) compared with the subgroup with 2 or more metabolic disorders (P=0.10; slope estimate, -0.08) and in those with non-insulin-dependent diabetes mellitus (P=0.46; slope estimate, -0.04). Although PAP reflects reactive fibrinolysis and is associated with subclinical atherosclerosis, this relationship may be weaker in populations with characteristics of the IRS, possibly reflecting the inhibitory effects of plasminogen activator inhibitor-1 on PAP. Decreased fibrinolysis in the presence of subclinical disease in subjects with hyperinsulinemia or glucose intolerance is consistent with the premise that depressed plasmin generation may enhance the progression of atherosclerosis in these people.
Keywords: Aged; Aged, 80 and over; alpha-2-Antiplasmin; Antifibrinolytic Agents; Asian Continental Ancestry Group; Cohort Studies; Coronary Disease; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Female; Fibrinolysin; Fibrinolysis; Humans; Insulin Resistance; Male; Multivariate Analysis; Myocardial Infarction; Plasminogen Activator Inhibitor 1; Risk Factors

Chlamydia pneumoniae, herpes simplex virus type 1, and cytomegalovirus and incident myocardial infarction and coronary heart disease death in older adults : the Cardiovascular Health Study. - Siscovick, D S; Schwartz, S M; Corey, L; Grayston, J T; Ashley, R; Wang, S P; Psaty, B M; Tracy, R P; Kuller, L H; Kronmal, R A (Circulation, 2000)
BACKGROUND: Whether serological evidence of prior infection with Chlamydia pneumoniae, herpes simplex virus type 1 (HSV-1), and cytomegalovirus (CMV) is associated with myocardial infarction (MI) and coronary heart disease (CHD) death remains a source of controversy. METHODS AND RESULTS: We conducted a nested case-control study among participants in the Cardiovascular Health Study, a cohort study of persons aged >/=65 years. Cases experienced an incident MI and CHD death (n=213). Control subjects were matched to cases by age, sex, clinic, year of enrollment, and month of blood draw (n=405). Serum was analyzed for IgG antibodies to C pneumoniae, HSV-1, and CMV. After adjustment for other risk factors, the risk of MI and CHD death was associated with the presence of IgG antibodies to HSV-1 (odds ratio [OR] 2.0, 95% CI 1.1 to 3.6) but was not associated with the presence of IgG antibodies to either C pneumoniae (OR 1.1, 95% CI 0.7 to 1.8) or CMV (OR 1.2, 95% CI 0.7 to 1.9). Although there was little association with low to moderate C pneumoniae antibody titers (</=1:512), high-titer (1:1024) C pneumoniae antibody was associated with an increased risk (OR 2.2, 95% CI 1.1 to 4.4). CONCLUSIONS: Among older adults, the presence of IgG antibodies to HSV-1 was associated with a 2-fold increase in the risk of incident MI and CHD death. For C pneumoniae, only high-titer IgG antibodies were associated with an increased risk of MI and CHD death. The presence of IgG antibodies to CMV was not associated with risk among the elderly.
Keywords: Adult; Age Factors; Aged; Antibodies, Bacterial; Antibodies, Viral; Case-Control Studies; Chlamydophila pneumoniae; Coronary Disease; Cytomegalovirus; Female; Herpesvirus 1, Human; HIV Antibodies; Humans; Immunoglobulin G; Male; Myocardial Infarction; Risk Factors

Clustering of procoagulation, inflammation, and fibrinolysis variables with metabolic factors in insulin resistance syndrome. - Sakkinen, P A; Wahl, P; Cushman, M; Lewis, M R; Tracy, R P (Am J Epidemiol, 2000)
The known metabolic cardiovascular disease risk factors associated with insulin resistance syndrome (IRS) do not adequately explain the excess cardiovascular disease risk attributed to this syndrome, and abnormalities in hemostatic variables may contribute to this excess risk. Using data from 322 nondiabetic elderly men and women (aged 65-100 years) participating in the Cardiovascular Health Study during 1989-1990, the authors performed factor analysis on 10 metabolic risk factors associated with IRS and 11 procoagulation, inflammation, and fibrinolysis variables to examine the clustering of the metabolic and hemostatic risk markers. Factor analysis of the metabolic variables confirmed four uncorrelated factors: body mass, insulin/glucose, lipids, and blood pressure. Adding the hemostatic variables yielded three new factors interpreted as inflammation, vitamin K-dependent proteins, and procoagulant activity. Plasminogen activator inhibitor-1 clustered with the body mass factor, supporting the hypothesis that obesity is related to impaired fibrinolysis. Fibrinogen clustered with the inflammation summary factor rather than procoagulant activity, supporting the position that fibrinogen principally reflects underlying inflammation rather than procoagulant potential. The authors conclude that should hemostatic variables be shown to contribute to IRS-related cardiovascular disease, apart from plasminogen activator inhibitor-1, they may do so independently of the established metabolic abnormalities.
Keywords: Aged; Aged, 80 and over; Antigens; Blood Coagulation; Cardiovascular Diseases; Cluster Analysis; Factor Analysis, Statistical; Factor VII; Female; Fibrinogen; Fibrinolysis; Humans; Inflammation; Insulin Resistance; Male; Middle Aged; Plasminogen Activator Inhibitor 1; Risk Factors

Predictors of congestive heart failure in the elderly: the Cardiovascular Health Study. - Gottdiener, J S; Arnold, A M; Aurigemma, G P; Polak, J F; Tracy, R P; Kitzman, D W; Gardin, J M; Rutledge, J E; Boineau, R C (J Am Coll Cardiol, 2000)
OBJECTIVES: We sought to characterize the predictors of incident congestive heart failure (CHF), as determined by central adjudication, in a community-based elderly population. BACKGROUND: The elderly constitute a growing proportion of patients admitted to the hospital with CHF, and CHF is a leading source of morbidity and mortality in this group. Elderly patients differ from younger individuals diagnosed with CHF in terms of biologic characteristics. METHODS: We analyzed data from the Cardiovascular Health Study, a prospective population-based study of 5,888 elderly people >65 years old (average 73 +/- 5, range 65 to 100) at four locations. Multiple laboratory measures of cardiovascular structure and function, blood chemistries and functional assessments were obtained. RESULTS: During an average follow-up of 5.5 years (median 6.3), 597 participants developed incident CHF (rate 19.3/1,000 person-years). The incidence of CHF increased progressively across age groups and was greater in men than in women. On multivariate analysis, other independent predictors included prevalent coronary heart disease, stroke or transient ischemic attack at baseline, diabetes, systolic blood pressure (BP), forced expiratory volume 1 s, creatinine >1.4 mg/dl, C-reactive protein, ankle-arm index <0.9, atrial fibrillation, electrocardiographic (ECG) left ventricular (LV) mass, ECG ST-T segment abnormality, internal carotid artery wall thickness and decreased LV systolic function. Population-attributable risk, determined from predictors of risk and prevalence, was relatively high for prevalent coronary heart disease (13.1%), systolic BP > or =140 mm Hg (12.8%) and a high level of C-reactive protein (9.7%), but was low for subnormal LV function (4.1%) and atrial fibrillation (2.2%). CONCLUSIONS: The incidence of CHF is high in the elderly and is related mainly to age, gender, clinical and subclinical coronary heart disease, systolic BP and inflammation. Despite the high relative risk of subnormal systolic LV function and atrial fibrillation, the actual population risk of these for CHF is small because of their relatively low prevalence in community-dwelling elderly people.
Keywords: Aged; Aged, 80 and over; Coronary Disease; Female; Geriatric Assessment; Heart Failure; Humans; Ischemic Attack, Transient; Male; Prospective Studies; Risk Factors; Survival Rate

Association between physical activity and markers of inflammation in a healthy elderly population. - Geffken, D F; Cushman, M; Burke, G L; Polak, J F; Sakkinen, P A; Tracy, R P (Am J Epidemiol, 2001)
Higher levels of physical activity are associated with lower risk of cardiovascular disease. There is growing evidence that the development of the atherosclerotic plaque is associated with inflammation. In this study, the authors investigated the cross-sectional association between physical activity and markers of inflammation in a healthy elderly population. Data obtained in 1989-1990 and 1992-1993 from the Cardiovascular Health Study, a cohort of 5,888 men and women aged >/=65 years, were analyzed. Concentrations of the inflammation markers-C-reactive protein, fibrinogen, Factor VIII activity, white blood cells, and albumin-were compared cross-sectionally by quartile of self-reported physical activity. Compared with persons in the lowest quartile, those in the highest quartile of physical activity had 19%, 6%, 4%, and 3% lower concentrations of C-reactive protein, white blood cells, fibrinogen, and Factor VIII activity, respectively, after adjustment for gender, the presence of cardiovascular disease, age, race, smoking, body mass index, diabetes, and hypertension. Multivariate regression models suggested that the association of higher levels of physical activity with lower levels of inflammation markers may be mediated by body mass index and glucose. There was no association between physical activity and albumin. Higher levels of physical activity were associated with lower concentrations of four out of five inflammation markers in this elderly cohort. These data suggest that increased exercise is associated with reduced inflammation. Prospective studies will be required for verification of these findings.
Keywords: Aged; Analysis of Variance; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Factor VIII; Female; Fibrinogen; Humans; Inflammation; Leukocyte Count; Male; Physical Exertion; Sex Factors; Smoking

The relation of markers of inflammation to the development of glucose disorders in the elderly: the Cardiovascular Health Study. - Barzilay, J I; Abraham, L; Heckbert, S R; Cushman, M; Kuller, L H; Resnick, H E; Tracy, R P (Diabetes, 2001)
Several studies suggest that inflammation plays a role in the pathogenesis of some glucose disorders in adults. We tested this hypothesis in a longitudinal cohort study of older individuals who had normal fasting glucose (FG) values at baseline. We compared the baseline levels of six inflammatory markers in participants who had developed glucose disorders at follow-up with those of participants whose FG remained normal at follow-up. Participants were members of the Cardiovascular Health Study, a prospective study of risk factors for cardiovascular disease in adults > or =65 years. All 5,888 participants had baseline testing, including FG and markers of inflammation: white blood cell and platelet counts and albumin, fibrinogen, C-reactive protein (CRP), and factor VIIIc levels. At 3-4 years of follow-up, 4,481 (84.5%) of those who were alive had FG levels retested. Participants who developed diabetes (n = 45) had higher median levels of CRP at baseline than those who remained normoglycemic. On multivariate analysis, those with elevated CRP levels (75th percentile [2.86 mg/l] vs. 25th percentile [0.82 mg/l]) were 2.03 times (95% confidence intervals, 1.44-2.86) more likely to have diabetes on follow-up. Adjustment for confounders and other inflammatory markers did not appreciably change this finding. There was no relationship between the development of diabetes and other markers of inflammation. Inflammation, as measured by CRP levels, is associated with the development of diabetes in the elderly. Understanding the role of inflammation in the pathogenesis of glucose disorders in this age-group may lead to better classification and treatment of glucose disorders among them.
Keywords: Aged; Biomarkers; Blood Glucose; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; Diabetes Mellitus; Female; Humans; Hypoglycemia; Inflammation; Longitudinal Studies; Male; Reference Values; Risk Factors

Lack of association of the plasminogen activator inhibitor-1 4G/5G promoter polymorphism with cardiovascular disease in the elderly. - Crainich, P; Jenny, N S; Tang, Z; Arnold, A M; Kuller, L H; Manolio, T; Sharrett, A R; Tracy, R P (J Thromb Haemost, 2003)
Elevated circulating plasminogen activator inhibitor-1 (PAI-1) may increase risk of cardiovascular disease (CVD). The 4G allele of the 4G/5G PAI-1 promoter polymorphism is associated with higher levels of PAI-1. We examined the association of PAI-1 4G/5G genotype and CVD events in the elderly participants of the Cardiovascular Health Study (CHS). We measured 4G/5G genotype in a nested case-control study within the CHS. Cases included incident angina, myocardial infarction (MI), and stroke. 4G/5G genotype was not found to be associated with markers of fibrinolysis or CVD risk in the selected elderly cohort. There were no differences in genotype frequencies by case-control status (5G/5G frequency 16-22%; chi2P= 0.07). The 5G allele was not associated with incident CVD events when individuals with at least one 5G allele were compared to 4G/4G homozygotes. The presence of at least one 4G allele was likewise not associated with incident CVD when those with 4G/4G and 4G/5G genotypes were compared to 5G/5G homozygotes. Our results suggest that the PAI-1 4G/5G promoter polymorphism is not associated CVD risk factors or incident CVD events in the elderly.
Keywords: African Continental Ancestry Group; Aged; Alleles; Cardiovascular Diseases; Case-Control Studies; Cohort Studies; European Continental Ancestry Group; Female; Genotype; Homozygote; Humans; Male; Myocardial Infarction; Plasminogen Activator Inhibitor 1; Polymorphism, Genetic; Promoter Regions, Genetic; Risk

Respiratory muscle strength and the risk of incident cardiovascular events. - van der Palen, J; Rea, T D; Manolio, T A; Lumley, T; Newman, A B; Tracy, R P; Enright, P L; Psaty, B M (Thorax, 2004)
BACKGROUND: Maximal inspiratory pressure (MIP) is a measure of inspiratory muscle strength. The prognostic importance of MIP for cardiovascular events among elderly community dwelling individuals is unknown. Diminished forced vital capacity (FVC) is a risk factor for cardiovascular events which remains largely unexplained. METHODS: MIP was measured at the baseline examination of the Cardiovascular Health Study. Participants had to be free of prevalent congestive heart failure (CHF), myocardial infarction (MI), and stroke. RESULTS: Subjects in the lowest quintile of MIP had a 1.5-fold increased risk of MI (HR 1.48, 95% CI 1.07 to 2.06) and cardiovascular disease (CVD) death (HR 1.54, 95% CI 1.09 to 2.15) after adjustment for non-pulmonary function covariates. There was a potential inverse relationship with stroke (HR 1.36, 95% CI 0.97 to 1.90), but there was little evidence of an association between MIP and CHF (HR 1.22, 95% CI 0.93 to 1.60). The addition of FVC to models attenuated the HR associated with MIP only modestly; similarly, addition of MIP attenuated the HR associated with FVC only modestly. CONCLUSIONS: A reduced MIP is an independent risk factor for MI and CVD death, and a suggestion of an increased risk for stroke. This association with MIP appeared to be mediated through mechanisms other than inflammation.
Keywords: Cardiovascular Diseases; Female; Follow-Up Studies; Forced Expiratory Volume; Humans; Male; Maximal Voluntary Ventilation; Prospective Studies; Respiratory Muscles; Risk Factors; Vital Capacity

Soluble intracellular adhesion molecule-1 is associated with cardiovascular disease risk and mortality in older adults. - Jenny, N S; Arnold, A M; Kuller, L H; Sharrett, A R; Fried, L P; Psaty, B M; Tracy, R P (J Thromb Haemost, 2006)
BACKGROUND: Intracellular adhesion molecule-1 (ICAM-1) regulates leukocyte-endothelial attachment, a process crucial to atherosclerosis. Circulating soluble ICAM-1 (sICAM-1) may serve as a marker of cardiovascular disease (CVD) progression. OBJECTIVES: We examined the association of sICAM-1 with measures of subclinical CVD and risk of incident CVD events and death in older men and women (age > or = 65 years) from the Cardiovascular Health Study. METHODS: Selected participants were free of clinical CVD at baseline. Non-exclusive incident case groups were angina (n = 534), myocardial infarction (n = 304), stroke (n = 327), and death (n = 842; CVD death = 310). A total 643 subjects were free of events during follow-up. RESULTS: sICAM-1 was positively associated with C-reactive protein, interleukin-6 and fibrinogen and measures of subclinical CVD in these older men and women. In Cox regression models adjusted for age, gender, and race, increasing levels of sICAM-1 were associated with increased risk of all cause mortality in men and women. Hazard ratios (95% confidence intervals) for a one standard deviation increase in sICAM-1 (89.7 ng mL(-1)) were 1.3 (1.1-1.4) in men and 1.2 (1.1-1.3) in women. sICAM-1 was associated with increased risk of CVD death in women (1.2; 1.0-1.5), but not men (1.1; 0.9-1.3). There were no associations of sICAM-1 with non-fatal CVD events. CONCLUSIONS: While sICAM-1 was associated with death in older men and women, there was a more marked association between sICAM-1 and CVD death in women.
Keywords: Aged; Aged, 80 and over; Angina Pectoris; Biomarkers; Cardiovascular Diseases; Female; Humans; Incidence; Intercellular Adhesion Molecule-1; Male; Mortality; Myocardial Infarction; Regression Analysis; Risk Factors; Sex Factors; Solubility; Stroke

Systematically missing confounders in individual participant data meta-analysis of observational cohort studies. - Jackson, Dan; White, Ian; Kostis, J B; Wilson, A C; Folsom, A R; Wu, K; Chambless, L; Benderly, M; Goldbourt, U; Willeit, J; Kiechl, S; Yarnell, J W G; et al. (Stat Med, 2009)
One difficulty in performing meta-analyses of observational cohort studies is that the availability of confounders may vary between cohorts, so that some cohorts provide fully adjusted analyses while others only provide partially adjusted analyses. Commonly, analyses of the association between an exposure and disease either are restricted to cohorts with full confounder information, or use all cohorts but do not fully adjust for confounding. We propose using a bivariate random-effects meta-analysis model to use information from all available cohorts while still adjusting for all the potential confounders. Our method uses both the fully adjusted and the partially adjusted estimated effects in the cohorts with full confounder information, together with an estimate of their within-cohort correlation. The method is applied to estimate the association between fibrinogen level and coronary heart disease incidence using data from 154,012 participants in 31 cohorts
Keywords: Cohort Studies; Computer Simulation; Coronary Disease; Data Interpretation, Statistical; Female; Fibrinogen; Humans; Male; Meta-Analysis as Topic; Models, Statistical

Adhesion molecules, endothelin-1 and lung function in seven population-based cohorts. - Oelsner, E C; Pottinger, T D; Burkart, K M; Allison, M; Buxbaum, S G; Hansel, N N; Kumar, R; Larkin, E K; Lange, L A; Loehr, L R; London, S J; O'Connor, G T; et al. (Biomarkers, 2013)
CONTEXT: Endothelial function is abnormal in chronic obstructive pulmonary disease (COPD); whether endothelial dysfunction causes COPD is unknown. OBJECTIVE: Test associations of endothelial biomarkers with FEV1 using instrumental variables. METHODS: Among 26 907 participants with spirometry, ICAM-1, P-selectin, E-selectin and endothelin-1 were measured in subsets. RESULTS: ICAM-1 and P-selectin were inversely associated with FEV1 among European-Americans (-29 mL and -34 mL per standard deviation of log-transformed biomarker, p < 0.001), as was endothelin-1 among African-Americans (-22 mL, p = 0.008). Genetically-estimated ICAM-1 and P-selectin were not significantly associated with FEV1. The instrumental variable for endothelin-1 was non-informative. CONCLUSION: Although ICAM-1, P-selectin and endothelin-1 were inversely associated with FEV1, associations for ICAM-1 and P-selectin do not appear causal.
Keywords: African Continental Ancestry Group; Biomarkers; Cohort Studies; E-Selectin; Endothelin-1; Endothelium, Vascular; European Continental Ancestry Group; Female; Gene Expression; Humans; Intercellular Adhesion Molecule-1; Lung; Male; Middle Aged; P-Selectin; Pulmonary Disease, Chronic Obstructive; Respiratory Function Tests; Spirometry

Prediction and classification of cardiovascular disease risk in older adults with diabetes. - Mukamal, K J; Kizer, J R; Djoussé, L; Ix, J H; Zieman, S; Siscovick, D S; Sibley, C T; Tracy, R P; Arnold, A M (Diabetologia, 2013)
AIMS/HYPOTHESIS: We sought to derive and validate a cardiovascular disease (CVD) prediction algorithm for older adults with diabetes, and evaluate the incremental benefit of adding novel circulating biomarkers and measures of subclinical atherosclerosis. METHODS: As part of the Cardiovascular Health Study (CHS), a population-based cohort of adults aged ≥65 years, we examined the 10 year risk of myocardial infarction, stroke and cardiovascular death in 782 older adults with diabetes, in whom 265 events occurred. We validated predictive models in 843 adults with diabetes, who were followed for 7 years in a second cohort, the Multi-Ethnic Study of Atherosclerosis (MESA); here 71 events occurred. RESULTS: The best fitting standard model included age, smoking, systolic blood pressure, total and HDL-cholesterol, creatinine and the use of glucose-lowering agents; however, this model had a C statistic of 0.64 and poorly classified risk in men. Novel biomarkers did not improve discrimination or classification. The addition of ankle-brachial index, electrocardiographic left ventricular hypertrophy and internal carotid intima-media thickness modestly improved discrimination (C statistic 0.68; p = 0.002) and classification (net reclassification improvement [NRI] 0.12; p = 0.01), mainly in those remaining free of CVD. Results were qualitatively similar in the MESA, with a change in C statistic from 0.65 to 0.68 and an NRI of 0.09 upon inclusion of subclinical disease measures. CONCLUSIONS/INTERPRETATION: Standard clinical risk factors and novel biomarkers poorly discriminate and classify CVD risk in older adults with diabetes. The inclusion of subclinical atherosclerotic measures modestly improves these features, but to develop more robust risk prediction, a better understanding of the pathophysiology and determinants of CVD in this patient group is needed.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Biomarkers; Blood Pressure; Cardiovascular Diseases; Carotid Intima-Media Thickness; Cholesterol, HDL; Diabetes Mellitus; Female; Humans; Male; Myocardial Infarction; Regression Analysis; Risk Factors; Stroke

Novel gene variants predict serum levels of the cytokines IL-18 and IL-1ra in older adults. - Matteini, A M; Li, J; Lange, E M; Tanaka, T; Lange, L A; Tracy, R P; Wang, Y; Biggs, M L; Arking, D E; Fallin, M D; Chakravarti, A; Psaty, B M; et al. (Cytokine, 2014)
Activation of inflammatory pathways measured by serum inflammatory markers such as interleukin-18 (IL-18) and interleukin-1 receptor antagonist (IL-1ra) is strongly associated with the progression of chronic disease states in older adults. Given that these serum cytokine levels are in part a heritable trait, genetic variation may predict increased serum levels. Using the Cardiovascular Health Study and InCHIANTI cohorts, a genome-wide association study was performed to identify genetic variants that influence IL-18 and IL-1ra serum levels among older adults. Multiple linear regression models characterized the association between each SNP and log-transformed cytokine values. Tests for multiple independent signals within statistically significant loci were performed using haplotype analysis and regression models conditional on lead SNP in each region. Multiple SNPs were associated with these cytokines with genome-wide significance, including SNPs in the IL-18-BCO gene region of chromosome 2 for IL-18 (top SNP rs2250417, P=1.9×10(-32)) and in the IL-1 gene family region of chromosome 2 for IL-1ra (rs6743376, P=2.3×10(-26)). Haplotype tests and conditional linear regression models showed evidence of multiple independent signals in these regions. Serum IL-18 levels were also associated with a region on chromosome 2 containing the NLRC4 gene (rs12989936, P=2.7×10(-19)). These data characterize multiple robust genetic signals that influence IL-18 and IL-1ra cytokine production. In particular, the signal for serum IL-18 located on chromosome two is novel and potentially important in inflammasome triggered chronic activation of inflammation in older adults. Replication in independent cohorts is an important next step, as well as molecular studies to better understand the role of NLRC4.
Keywords: Aged; Aged, 80 and over; Calcium-Binding Proteins; CARD Signaling Adaptor Proteins; Chromosomes, Human, Pair 2; Female; Genetic Variation; Genome-Wide Association Study; Genotype; Haplotypes; Humans; Inflammation; Interleukin 1 Receptor Antagonist Protein; Interleukin-18; Male; Polymorphism, Single Nucleotide

Physical activity, inflammation, and volume of the aging brain. - Braskie, M N; Boyle, C P; Rajagopalan, P; Gutman, B A; Toga, A W; Raji, C A; Tracy, R P; Kuller, L H; Becker, J T; Lopez, O L; Thompson, P M (Neuroscience, 2014)
Physical activity influences inflammation, and both affect brain structure and Alzheimer's disease (AD) risk. We hypothesized that older adults with greater reported physical activity intensity and lower serum levels of the inflammatory marker tumor necrosis factor α (TNFα) would have larger regional brain volumes on subsequent magnetic resonance imaging (MRI) scans. In 43 cognitively intact older adults (79.3±4.8 years) and 39 patients with AD (81.9±5.1 years at the time of MRI) participating in the Cardiovascular Health Study, we examined year-1 reported physical activity intensity, year-5 blood serum TNFα measures, and year-9 volumetric brain MRI scans. We examined how prior physical activity intensity and TNFα related to subsequent total and regional brain volumes. Physical activity intensity was measured using the modified Minnesota Leisure Time Physical Activities questionnaire at year 1 of the study, when all subjects included here were cognitively intact. Stability of measures was established for exercise intensity over 9 years and TNFα over 3 years in a subset of subjects who had these measurements at multiple time points. When considered together, more intense physical activity intensity and lower serum TNFα were both associated with greater total brain volume on follow-up MRI scans. TNFα, but not physical activity, was associated with regional volumes of the inferior parietal lobule, a region previously associated with inflammation in AD patients. Physical activity and TNFα may independently influence brain structure in older adults.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Apolipoproteins E; Brain; Female; Humans; Inflammation; Longitudinal Studies; Magnetic Resonance Imaging; Male; Motor Activity; Neuroimmunomodulation; Neuropsychological Tests; Organ Size; Parietal Lobe; Surveys and Questionnaires; Tumor Necrosis Factor-alpha

Coagulation factor XII genetic variation, ex vivo thrombin generation, and stroke risk in the elderly: results from the Cardiovascular Health Study. - Olson, N C; Butenas, S; Lange, L A; Lange, E M; Cushman, M; Jenny, N S; Walston, J; Souto, J C; Soria, J M; Chauhan, G; Debette, S; Longstreth, W T; et al. (J Thromb Haemost, 2015)
BACKGROUND: The relationships of thrombin generation (TG) with cardiovascular disease risk are underevaluated in population-based cohorts. OBJECTIVES: To evaluate the relationships of TG influenced by the contact and tissue factor coagulation pathways ex vivo with common single-nucleotide polymorphisms (SNPs) and incident cardiovascular disease and stroke. PATIENTS/METHODS: We measured peak TG (pTG) in baseline plasma samples of Cardiovascular Health Study participants (n = 5411), both with and without inhibitory anti-factor XIa antibody (pTG/FXIa(-) ). We evaluated their associations with ~ 50 000 SNPs by using the IBCv2 genotyping array, and with incident cardiovascular disease and stroke events over a median follow-up of 13.2 years. RESULTS: The minor allele for an SNP in the FXII gene (F12), rs1801020, was associated with lower pTG in European-Americans (β = - 34.2 ± 3.5 nm; P = 3.3 × 10(-22) ; minor allele frequency [MAF] = 0.23) and African-Americans (β = - 31.1 ± 7.9 nm; P = 9.0 × 10(-5) ; MAF = 0.42). Lower FXIa-independent pTG (pTG/FXIa(-) ) was associated with the F12 rs1801020 minor allele, and higher pTG/FXIa(-) was associated with the ABO SNP rs657152 minor allele (β = 16.3 nm; P = 4.3 × 10(-9) ; MAF = 0.37). The risk factor-adjusted ischemic stroke hazard ratios were 1.09 (95% confidence interval CI 1.01-1.17; P = 0.03) for pTG, 1.06 (95% CI 0.98-1.15; P = 0.17) for pTG/FXIa(-) , and 1.11 (95% CI 1.02-1.21; P = 0.02) for FXIa-dependent pTG (pTG/FXIa(+) ), per one standard deviation increment (n = 834 ischemic strokes). In a multicohort candidate gene analysis, rs1801020 was not associated with incident ischemic stroke (β = - 0.02; standard error = 0.08; P = 0.81). CONCLUSIONS: These results support the importance of contact activation pathway-dependent TG as a risk factor for ischemic stroke, and indicate the importance of F12 SNPs for TG ex vivo and in vivo.
Keywords: African Americans; Age Factors; Aged; Blood Coagulation; Brain Ischemia; European Continental Ancestry Group; Factor XII; Female; Gene Frequency; Genetic Predisposition to Disease; Humans; Incidence; Male; Phenotype; Polymorphism, Single Nucleotide; Prospective Studies; Risk Assessment; Risk Factors; Stroke; Thrombin; Time Factors; United States